PHYTOESTROGEN IN SEVERAL FRUITS AND LEAVES - L. Maha putra; Hening Laswati putra (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Phytoestrogen is molecularly almost similar with and acts the same as estrogen and is found a lot in several fruits and leaves grown either in tropical or subtropical countries. However, the quantity of molecular contents are not yet known exactly. In menopause and andropause, people need substitution of estrogens as a replacement therapy of sex hormone, due to the significant hormone decline and impacted disturbance of several organ functions and thus progressively causing severe organ dysfunctions. The objective of this study was to know the estrogen content by analyzing extractions of pegaga, green clover leaves, tomato and papaya fruit of which certain communites have overviewed contents of the leaves and fruit The samples which were collected for this purpose used 10 times replication in four different groups: the pegaga, green clover leaves, tomato and papaya fruit. All these groups were divided into two (2) subgroups based on the process or subspecies. All samples were made as an infusion 1:4) w/v), and then extracted after centrifugation 1000xg for 15mnts, with 1:5 petroleum ether) v/v). After it was evaporated, each extraction then was kept dry-frozen at –20° C until the analysiswas performed. Solid phase Radioimmunoassay technique was used to identify the estrogen contents, up to a total of 80 samples The binding percentage of each sample was then interpolated on a logit-log paper to find out the real concentrations.14 The lowest estrogen level was found in fresh pegaga leaves extract (Mean+SD) was 47.9+5.5 pg/g, but in dry leaves extract the level was increased twice, about 96.1+11.2 pg/g. Meanwhile the estrogen level in fresh green clover leaves extract was 538.0+30.5 pg/g, more than ten times higher compared to fresh pegaga level, but twice lower than the estrogen level compared to dry green clover leaves extract, which was 1068.0+97.2 pg/g. In the fruit group, the fibrin part of tomatoes had more or less the same estrogen content compared with Thai papaya subspecies, 1037.0+37.7 pg/g and 1175.0+67.7 pg/g, respectively. On the other hand, it was noted that the inner part/fibrin part of tomato had a higher estrogen level of four (4) times compared to the outer part which was 315.0+18.4 pg/g. While it was noted that local Java papaya besides being not so sweet, the estrogen level was also not as high or the same as that found in fresh green clover which is 530.1+50.7 pg/g and 538.0+30.5 pg/g. Based on this study so far, it can be concluded that semanggi/green clover, tomato and papaya could be suggested as a replacement therapy for certain people who are considered to have reduced estrogen content, except that pegaga leaves are not recommended. The last mentioned plant besides that it is difficult to obtain, its estrogen content is also very low.